2013
DOI: 10.1097/ajp.0b013e31824ce65c
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and Affective Pain Descriptors Respond Differentially to Pharmacological Interventions in Neuropathic Conditions

Abstract: These results point to the hypothesis that sensory and affective pain descriptor profiles exhibit a treatment-specific response. Larger, more definitive, investigations to evaluate treatment-specific effects on multiple sensory and affective pain descriptors, and prediction of treatment response by these descriptors, will advance efforts toward developing and implementing more effective individualized pain therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The cognitive (termed evaluative in the MPQ) and affective descriptors were grouped into a single category because they both reflected the meaning an individual gives to their pain and/or negative emotions associated with pain, whereas sensory and neuropathic descriptors are more representative of physical sensations of pain. The division between sensory and affective categories is consistent with prior studies [19,26,42,55]. Repeated studies have reported certain pain qualities, i.e.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The cognitive (termed evaluative in the MPQ) and affective descriptors were grouped into a single category because they both reflected the meaning an individual gives to their pain and/or negative emotions associated with pain, whereas sensory and neuropathic descriptors are more representative of physical sensations of pain. The division between sensory and affective categories is consistent with prior studies [19,26,42,55]. Repeated studies have reported certain pain qualities, i.e.…”
Section: Discussionsupporting
confidence: 88%
“…The ability of pain qualities to discriminate between neuropathic (resulting from nerve injury or abnormal nerve functioning) and nociceptive (resulting from tissue injury) pain has been established using a diagnosis-based approach [11,36,43,56]. Further support for the relationship between pain quality and mechanisms of pain has been demonstrated by preferential improvement of specific pain qualities by pharmacological treatment [19,20]. Pain quality assessment for chronic geriatric pain, about which little is known, could capture information on mechanisms of pain in the setting of multiple pain-associated conditions and age-related effects on pain perception to develop more targeted prevention and intervention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates that self-report verbal pain descriptors, such as those in the NPS, depict important pain dimensions 36. The assessment of patterns of pain symptoms using descriptors might contribute to the identification of distinct pathophysiologic mechanisms and the development of mechanism-based treatment approaches 37.…”
Section: Discussionmentioning
confidence: 99%
“…Multidimensional measures are strongly recommended for outcome measures of pain management in clinical trials [16], are very widely used in assessing pain in patients [17], and are widely used in basic pain research. Multidimensional tools have revealed phenomena invisible to unidimensional scales; for instance, they have shown different profiles of pain in different categories of patients [18], and have shown that sensory and affective dimensions can respond differentially to treatment [1921]. The main elements of the multidimensional pain model are the sensory quality, sensory intensity, unpleasantness, and emotional impact; other elements included location and temporal properties.…”
Section: Introductionmentioning
confidence: 99%